Clinical Trial Of Ketoconazole 2% + Zinc Pyrithione 1% Shampoo In The Management Of Tinea Versicolor - Ramesh M; Bhat Aparna; Shetty Sohandas (Wolters Kluwer Medknow Publications, 2004)
An open uncontrolled trial, to assess the efficacy of ketoconazole 2%+zinc pyrithione 1% shampoo was conducted in patients with extensive tinea versicolor. The results show that this is an effective and well tolerated combination in the management of tinea versicolor.